The Impact of Covid-19 on the State Audit in the Republic of North Macedonia – Lessons from the Crisis - Dionisijev, Ivan; Bozhinovska Lazarevska, Zorica (Audit Financiar, 2022)
The COVID-19 pandemic has left no area in the society that has not been affected. For auditing the spending of public money, especially in times of uncertainties imposed by the COVID-19 pandemic, the state audit is a crucial factor, hence the synonym for state audit is "watchdog of public money". The activities related to the state audit in the Republic of North Macedonia are performed by the State Audit Office (SAO), as the Supreme Audit Institution. This paper attempts to investigate the impact of the COVID-19 pandemic on the state audit in the Republic of North Macedonia, through the state auditors' perception of the COVID-19 pandemic impact on the dynamics and the scope of SAO activities, with a special focus on ethical dilemmas and expectations for the post covid period and what have the state auditors specifically learned from the crisis. For that purpose, a structured and detailed survey was submitted to all state auditors in the Republic of North Macedonia, covering all aspects of the audit process, the independence of the State Audit Office, changes in the environment, and the post-covid period. The obtained answers are analyzed through `descriptive statistics` and `analysis of variance`. In general, it can be concluded that the state auditors have retained their independence and the quality of conducting audits during the pandemic.
Keywords: COVID-19; "black swan" event; state auditor; independence; technology